2017
DOI: 10.3390/en10020259
|View full text |Cite
|
Sign up to set email alerts
|

A Nafion-Ceria Composite Membrane Electrolyte for Reduced Methanol Crossover in Direct Methanol Fuel Cells

Abstract: An alternative Nafion composite membrane was prepared by incorporating various loadings of CeO 2 nanoparticles into the Nafion matrix and evaluated its potential application in direct methanol fuel cells (DMFCs). The effects of CeO 2 in the Nafion matrix were systematically studied in terms of surface morphology, thermal and mechanical stability, proton conductivity and methanol permeability. The composite membrane with optimum filler content (1 wt. % CeO 2 ) exhibits a proton conductivity of 176 mS·cm −1 at 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 29 publications
(38 reference statements)
0
20
0
Order By: Relevance
“…For instance, Bellucci et al demonstrated that the optical properties changes were correlated to nanoparticle-driven interface modulations [1]. The potential uses of composites include battery cathodes and solid-state ionics [2,3], supercapacitor and dielectrics [4,5], catalysts [6,7], corrosion protection [8,9], sensors [10], optical and electrical materials [11,12], ultraviolet (UV) blocking [13,14,15] and many others. In these recent years, composites with the use of organic–inorganic hybrids were found to possess improved and new properties.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Bellucci et al demonstrated that the optical properties changes were correlated to nanoparticle-driven interface modulations [1]. The potential uses of composites include battery cathodes and solid-state ionics [2,3], supercapacitor and dielectrics [4,5], catalysts [6,7], corrosion protection [8,9], sensors [10], optical and electrical materials [11,12], ultraviolet (UV) blocking [13,14,15] and many others. In these recent years, composites with the use of organic–inorganic hybrids were found to possess improved and new properties.…”
Section: Introductionmentioning
confidence: 99%
“…4(a) and (b). More roughness on modified Nafion ® nanocomposite membranes improves the contact between the electrodes [31]. The modified membranes show the presence of ZrO 2 -CNT in the surface of membrane, which can be assigned to the hydrophobic (light regions)/hydrophilic (dark regions) domains across the membrane matrix due to the interaction of the sulphonic groups dispersed within the hydrophobic network of the Nafion ® polymeric backbone [32].…”
Section: Resultsmentioning
confidence: 98%
“…Since the composite membranes were designed to allow operation of a DMFC (or a PEFC) at temperatures higher than 90–100 °C [ 38 , 39 ], reducing the drawback of membrane dehydration at those temperatures with consequent loss of conductivity. The influence of the CTO filler on the electrochemical behavior of the membrane in DMFC at 110 °C has been evaluated, and the results are reported in Figure 7 .…”
Section: Resultsmentioning
confidence: 99%